Dampak Pelatihan Dan Lingkungan Kerja Fisik Terhadap Kinerja Karyawan Pada PT Bintang Yoga Indonesia Di Jakarta Utara - Amelia Putri Nazma; Abdul Rahman Safiih (JURNAL AKADEMIK EKONOMI DAN MANAJEMEN, 2025)
This study aims to determine the impact of training and physical work environment on employee performance at PT Bintang Yoga Indonesia, North Jakarta, both partially and simultaneously. The research method used in this study is quantitative research. The population in this study consists of employees of PT Bintang Yoga Indonesia, North Jakarta. The sampling method used by the researcher is the saturated sampling method, in which the sample includes all 53 employees of PT Bintang Yoga Indonesia, North Jakarta. The data collection method used is primary data, obtained from the responses of 53 respondents. The results of the study show that training and the physical work environment have a positive and significant impact on employee performance, as indicated by the regression equation Y = 6,610 + 0,596 X1 + 0,283 X2 Training has a partial effect on employee performance at PT Bintang Yoga Indonesia, North Jakarta, as evidenced by t-count > t-table (8.900 > 2.008), further supported by a Sig. value < 0.05 (0.000 < 0.05). Similarly, the physical work environment also has a partial effect on employee performance, proven by t-count > t-table (6.064 > 2.008), and a Sig. value < 0.05 (0.000 < 0.05). Training and physical work environment simultaneously have a significant effect on employee performance at PT Bintang Yoga Indonesia, North Jakarta, as evidenced by F-count > F-table (52.627 > 3.183), which is also supported by a Sig. value < 0.05 (0.000 < 0.05).